2022
DOI: 10.1177/00221856221111693
|View full text |Cite
|
Sign up to set email alerts
|

Decent gig work in Sub Sahara Africa?

Abstract: Sub-Saharan Africa (SSA) economies are entrenched in traditional economic and employment structures driven by the informal sector. There is a small and regulated formal sector, built upon public sector employment. Unlike the discussion of gig work in advanced capitalist economies, the development of gig work in SSA is within an environment where employment standards and labour regulations are largely absent. The concern in developed countries is that gig work erodes the norm of regulated employment; in develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…The foregoing quotations align with previous studies (e.g., Graham et al, 2017;Ayentimi et al, 2023) that argued that income is a crucial motivation for workers who take up jobs in the gig economy.…”
Section: Drivers' Career Choices and Motivations For Working On The P...supporting
confidence: 83%
See 1 more Smart Citation
“…The foregoing quotations align with previous studies (e.g., Graham et al, 2017;Ayentimi et al, 2023) that argued that income is a crucial motivation for workers who take up jobs in the gig economy.…”
Section: Drivers' Career Choices and Motivations For Working On The P...supporting
confidence: 83%
“…For instance, research has shown that gig workers are often attracted by the perceived autonomy, flexibility and task variety that digital platforms offer (Graham et al, 2017;Wood et al, 2019;Anwar and Graham, 2021). Other pull factors in African countries include the unemployment rate in the formal sector requiring individuals to engage in gig work for survival and high-income earnings from taking up multiple gig jobs (Ayentimi et al, 2023). On the other hand, push factors refer to the prevalent unfavourable forces that motivate individuals to leave their current work in the gig economy and pursue alternative opportunities.…”
Section: Algorithmic Management In the Gig Economymentioning
confidence: 99%
“…Researchers need to develop innovative research methods that can capture the nuances and complexities of digital labour and the ways in which it shapes work and employment. Hence, digital labour has significant policy implications for labour markets, social protection and the regulation of work (Kirk et al , 2022; Yao et al , 2022; Ayentimi et al , 2023). Researchers need to engage with policymakers and other stakeholders, including businesses, to ensure that their research findings inform policy debates and decisions.…”
Section: Implications Of the Studymentioning
confidence: 99%
“…Services can be performed online (this is how platforms such as Useme, Freelancer, MTurk, PeoplePerHour and many others operate) or offline (examples of such platforms include Task Rabbit, Pomocedomowe, Uber, Glovo), but they are always me diated by a digital platform. They can range from typical simple jobs, referred to as crowd work, to assignments or projects requiring specialised knowledge, classified as freelancing, but they also include the work of couriers delivering meals, drivers transporting people, and contractors of simple domestic services and alike [De Stefano, 2015;Florisson, Mandl, 2018;Mandl, 2021;Stewart, Stanford, 2017;Ayentimi, Abadi, Burgess, 2023].…”
Section: Introductionmentioning
confidence: 99%